The Effect of Transaction Volume, Coupons, and Macro Variables on the Price of Retail State Sukuk in Indonesia - Faisal, Agus; Hidayani, Evy (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2023)
Purpose: This study aims to analyse transaction volume, coupons, exchange rates, economic growth and the BI rate. Methodology: The sample used in this study is Retail State Sukuk in Indonesia SR001-SR007. Variable transaction volume data, coupons obtained from The Indonesia Capital Market Institute. While for macro variable data (exchange rate, economic growth, and BI rate) obtained through publication www.bi.go.id. The number of observations used amounts to 264 data. The data analysis technique in this study is panel data regression analysis with E-views software 8. Findings: The results show variable coupons, exchange rates, and the BI rate have a significant effect on the price of Retail State Sukuk with a significant value probability <α = 5% (0.05). Whereas transaction volume and economic growth do not affect the price of Retail State Sukuk. This is because the income of each individual Indonesian society varies, so it does not affect the rise and fall of Retail State Sukuk. Novelty: This research wants to analyze the instruments that influence fluctuations in Retail Government Sukuk Prices in Indonesia SR001-SR007. using data on internal variables (transaction volume, coupons) and macro variables (exchange rate, economic growth and BI rate). The analysis technique in this research is panel data regression analysis and among its benefits is adding to the repertoire of Islamic finance, providing knowledge and considerations for sukuk investors.